PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM PADA SUB SEKTOR PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BEI PERIODE 2016 - 2020 - Atika Rahmi; Desti Suryaningtias (BALANCING: Accountancy Journal, 2022)
This study aims to determine the effect of Earning Per Share (EPS), Price Earning Ratio (PER) on stock prices. This research method is quantitative. This study uses secondary data from financial reports published on the Indonesia Stock Exchange (IDX). From the purposive sampling technique, 11 companies were obtained from the population of 65 companies in the property and real estate sub-sector. The results of this study indicate that EPS and PER partially or simultaneously have a significant positive effect on stock prices.